A Short Report Examining the Introduction of Routine Use of Patient-Reported Outcome Measures in a Mixed Oncology Population. Issue 4 (April 2022) - Stewart, E.; Tavabie, S.; White, N.; Appleyard, S.; Bass, S.; Gilbert, D.; Herriott, R.; Williams, T.; Wells, G.; Young, K.; Minton, O.
Abstract: Aims: People living with treatable but not curable cancer often experience a range of symptoms related to their cancer and its treatment. During the COVID-19 pandemic, face-to-face consultations were reduced and so remote monitoring of these needs was necessary. University Hospitals Sussex implemented the routine use of electronic remote patient-reported outcome measures (PROMs) in a mixed oncology population, focusing on those with treatable but not curable cancers. Materials and methods: Over a 9-month period, patients were invited to register with My Clinical Outcomes (MCO) – a secure online platform for the collection of electronic PROMs. They were prompted by e-mail to complete assessments (EORTC QLQ-C30, EQ-5D-3L and EQ-5D VAS) routinely every 2 weeks. The team monitored patient scores and changes in these prompted clinical interventions. Results: In total, 324 patients completed at least one assessment. The median number of assessments completed by each patient was eight. The most represented tumour groups were secondary breast (28%), prostate (25%) and other (32%). Median scores for the assessments did not deteriorate in a clinically or numerically significant way for patients living with non-curable conditions for the majority of patients monitored. Conclusion: Routine collection of electronic remote PROMs is an effective and useful strategy to provide real-time clinical feedback to teams. With integration into existing systems, online platforms (such as MCO) could provide efficient and patient-centred information for those providing care for people with cancer. Highlights: Electronic PROMs can be used in routine oncology care. Remote monitoring was beneficial during the COVID-19 pandemic. PROMs can be used to inform shared decision making and target specific interventions.